Clinical Practice Experiences Using a Professional Diabetes Management Ecosystem During COVID. (March 2023) - Merino Torres, Juan Francisco; Grady, Mike; Lopez Alba, Alfonso; Nattero Chavez, Lía; Justel Enriquez, Alicia; Gaspar, Ruth; Aizpeolea San Miguel, Lourdes; Menendez Alvarez, Flor; Nunes Pinto, Elsa; Petry, Friedrich Wilhelm; Jorn, Rose; Weyland, Maria; et al.
Background: Challenges of patient care in diabetes were exacerbated by COVID, undermining the ability of patients to engage in-person with health care professionals (HCPs). To combat this, there has been accelerated adoption of telemedicine to support patient and provider connectivity. Methods: We collated survey information regarding telemedicine from 21 European clinical institutions. Health care professionals joined virtual meetings focusing on the OneTouch Reveal (OTR) ecosystem and its utility for conducting telemedicine. Selected HCPs provided clinical case studies to explain how the OTR ecosystem supported patient care. Results: Remote consultations increased by nearly 50% in 21 European clinics during the pandemic (Belgium [24%], Iberia [65%], Germany [34%], Italy [54%]). In all, 52% of people with diabetes using OTR app to connect remotely with HCPs had type 1 diabetes and 48% had type 2 diabetes. Remote connection methods included telephone (60%), email (19%), video chat (10%), text only (3%), or a mix of these methods (8%). Health care professionals usually reviewed patient data during consultations (45%) rather than before consultations (25%). Fifty-five percent of HCPs indicated digital ecosystems like OTR ecosystem would become their standard of care for diabetes management. In-depth conversations with HCPs provided a deeper understanding of how a digital ecosystem integrated into clinical practice and population management. In addition, five patient case studies using OTR ecosystem were provided by a selection of our HCPs. Conclusion: Diabetes management solutions, such as OTR ecosystem, supported telemedicine during the pandemic and will continue to play a valuable role in patient care beyond the pandemic.